KINERJA BHABINKAMTIBMAS KELURAHAN PELANGIRAN KECAMATAN PELANGIRAN DALAM MEMELIHARA KAMTIBMAS - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
The purpose of this study was to determine and describe the performance of Babinkamtibmas, Pelangiran Village, Pelangiran District in maintaining Kamtibmas and to know and describe what factors affect the performance of Babinkamtibmas, Pelangiran Village, Pelangiran District in maintaining kamtibmas. Research activities are always carried out as an effort to understand and solve problems scientifically based on empirical facts. This research is a descriptive analytical study. Data collection techniques are carried out by interviewing and giving questionnaires to the pelangiran community. The data obtained through this study were processed and analyzed using qualitative normative analysis methods. The results of the study explain that the functions of Bhabinkamtibmas are counseling in the field of law and community service, community service on social security issues, fostering public order against prevailing norms, mediation and facilitation of problem-solving efforts and coordination of community service efforts. Some of the obstacles in creating kamtibmas are public knowledge about the implementation of Polri duties, especially Bhabinkamtibmas, the low level of community legal understanding, the actions of unprofessional police members so that public trust in Polri is still relatively low. The efforts that need to be made by the National Police in overcoming obstacles to the implementation of Bhabinkamtibmas In maintaining Kamtibmas include: Preemptive, preventive, repressive.